THE IDENTIFICATION OF ANTIBACTERIAL COMPOUNDS IN CLOVE STEM EXTRACT (Syzygium aromaticum) AND ITS EFFECTIVENESS IN INHIBITING THE GROWTH OF Escherichia coli - Yunita Diyah Safitri; Ana Amalia; Fatimah Fatimah; Afidatul Muadifah (Universitas Negeri Medan, 2022)
Clove plants usage in daily life is very diverse, such as kitchen spices, mixtures of various drinks, and medicines. Clove is a spice plant that contains clove oil which is known as an antibacterial agent. The clove stem has a fairly high clove oil content, but this is not widely known by the public. Clove oil is known to have the ability as a fungicide, bactericide, insecticide, and nematicide. The purpose of this study is to identify antibacterial compounds and the effectiveness of clove stem extract on the growth of Escherichia coli. We used GCMS (Gas Chromatography Mass Spectrometry) analysis to identification antibacterial compounds. Antibacterial activity test using paper disc method by measuring the diameter of the inhibition zone formed from clove stem extract at doses of 30%, 50%, and 70% against Escherichia coli. The results of the study were analyzed using ANOVA with significance (p<0.05). The identification of the active compound showed 13 kinds of compounds were found with the dominant compound was alpha-pinene. The results of the antibacterial test showed the antibacterial activity of clove stem extract at doses of 30%, 50% and 70% with inhibition zones formed 12 mm, 12.7 mm, and 14.1 mm respectively.